2023
DOI: 10.3390/molecules28176431
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biomedical Applications of Biosynthesized Silver Nanoparticles Using Perilla frutescens Flavonoid Extract: Antibacterial, Antioxidant, and Cell Toxicity Properties against Colon Cancer Cells

Tianyu Hou,
Yurong Guo,
Wanyu Han
et al.

Abstract: The present study reports the biomimetic synthesis of silver nanoparticles (AgNPs) using a simple, cost effective and eco-friendly method. In this method, the flavonoid extract of Perilla frutescens (PFFE) was used as a bioreduction agent for the reduction of metallic silver into nanosilver, called P. frutescens flavonoid extract silver nanoparticles (PFFE-AgNPs). The Ultraviolet–Visible (UV-Vis) spectrum showed a characteristic absorption peak at 440 nm that confirmed the synthesis of PFFE-AgNPs. A Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Other current studies reported the antibacterial efficiency of Ag NPs synthesized using the flavonoid extract of Perilla frutescens, Calvatia gigantea, Mycena leaiana, and Ocimum sanctum. These formulations showed significant inhibition of several pathogens, including Listeria monocytogens, Enterococcus faecalis, A. baumannii, Staphylococcus aureus, P. aeruginosa, K. pneumoniae, Proteus mirabilis, Enterobacter cloacae, and E. coli [21][22][23]. This research underscores the potential utility of Ag NPs in antimicrobial applications, particularly in addressing MDR strains.…”
Section: Introductionmentioning
confidence: 64%
“…Other current studies reported the antibacterial efficiency of Ag NPs synthesized using the flavonoid extract of Perilla frutescens, Calvatia gigantea, Mycena leaiana, and Ocimum sanctum. These formulations showed significant inhibition of several pathogens, including Listeria monocytogens, Enterococcus faecalis, A. baumannii, Staphylococcus aureus, P. aeruginosa, K. pneumoniae, Proteus mirabilis, Enterobacter cloacae, and E. coli [21][22][23]. This research underscores the potential utility of Ag NPs in antimicrobial applications, particularly in addressing MDR strains.…”
Section: Introductionmentioning
confidence: 64%
“…In line with our data, Panax ginseng Meyer-mediated AgNPs showed considerable anticancer effects on A549, MCF-7, and HepG2 cancer cells as revealed by heightened level of oxidative stress [ 29 ]. In contrast, some previous reports emphasized the antioxidant properties of AgNPs in which an enhancement of antioxidant enzymes such as SOD and CAT is reported [ 30 ]. In essence, the characteristic of nanoparticles might affect their final biological activity within cells [ 31 ].…”
Section: Discussionmentioning
confidence: 86%
“…The surface of VCS-CDs contains numerous oxygen-containing functional groups, making it susceptible to releasing hydrogen ions and rendering the solution negatively charged. Comparatively, carbon dots with negative charge exhibit lower toxicity ( Havrdova et al, 2016 ; Yan et al, 2018 ), and the negative potential of nanoparticles contributes to their in vivo dispersibility and stability ( Tang et al, 2023 ) and diminishes aggregation of the particles in the solution ( Hou et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%